Electrochemically chopped WS2 quantum dots as an efficient and stable electrocatalyst for water reduction. Issue 1 (7th December 2018) - Anantharaj, S.; Valappil, Manila O.; Karthick, K.; Pillai, Vijayamohanan K.; Alwarappan, Subbiah; Kundu, Subrata
Abstract : A single-step electrochemical disintegration of bulk WS2 led to a highly active WS2 QDs electrocatalyst for HER. Abstract : Advancements in the search for efficient H2 evolving electrocatalysts by engineering the structure and electronic properties of bulk materials at the nano regime have had a constructive impact on realizing better performance with ultralow catalyst loading. In this work, we investigate the electrochemical hydrogen evolution catalysis of WS2 quantum dots (QDs) synthesized electrochemically. WS2 QDs were evaluated for a hydrogen evolution reaction (HER) in 0.5 M H2 SO4 as a binder-less electrocatalyst, which necessitated a low HER onset of 190 mV and reached −200 mA cm −2 at 473 mV. In contrast, the bulk WS2 exhibited a poor performance, which required 780 mV to drive −50 mA cm −2 . The electrochemical disintegration of bulk WS2 into QDs is the key behind such activation.